Improving oral expression skills using the acquisition of language patterns among students with LDs - Mohamad Ahmad Saleem Khasawneh (PJE, 2023)
This study aimed at identifying the impact of learning language patterns appropriately on the development of oral expression skills among students with learning disabilities. The study used experimental and descriptive approaches. The instruments included a training program and an achievement test, which was applied before and after the application of the program. The sample of the study included 84 students with learning disabilities from Irbid city, Jordan. The results of the study found a positive correlation between the pre and post-tests. The study concluded that implementing the right training programs helps students to improve their academic levels and help the teacher to implement the right strategies